THE ROLE OF MUá¹¢ÄLAá¸¤AH IN CONFLICT RESOLUTION: A HISTORICAL PERSPECTIVE - Rusli, Rusli (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract. This paper deals with the role of muá¹£Älaá¸¥ah in conflic resolution among Muslim societies using a historical approach. From a historical analysis it is concluded that the concept of á¹£ulá¸¥ and muá¹£Älaá¸¥ah have predated Islam, and played a vital role in resolving disputes and conflicts among clans in pre-Islam Arab societies. In the period of Islam, as in the case of Fatá¸¥ Makkah (winning over Mecca) and á¹¢ulá¸¥ al-á¸¤udaybiyyah (peace treaty at á¸¤udaybiyyah). In resolving conflicts, there are principles employed by the Prophet Muá¸¥ammad, such as tolerance, non-violence, patience, forgiveness, peace, harmony and mercy.Kata Kunci: Â Â Â Â Â Â resolusi konflik, muá¹£Älaá¸¥ah, á¹£ulá¸¥, toleransi, nir-kekerasan, pemaafan